2011
DOI: 10.1007/s12199-011-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of ecological exposure of adult residents in Fukushima Prefecture to radioactive cesium through ingestion and inhalation

Abstract: ObjectiveThis study aims to estimate the ecological exposure of adult residents of Fukushima Prefecture to 134cesium (Cs) and 137Cs through ingestion and inhalation between July 2 and July 8, 2011.MethodsFifty-five sets of meals with tap water, each representing one person’s daily intake, were purchased in local towns in Fukushima Prefecture. Locally produced cow’s milk (21 samples) and vegetables (43 samples) were also purchased. In parallel, air sampling was conducted at 12 different sites using a high-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 5 publications
3
39
1
Order By: Relevance
“…Nevertheless, these radiation levels were much lower than external radiation dose rates. Participants' residences neighbor the restricted and evacuation areas and participants consume homegrown vegetables; however, the doses were comparable to those in our previous research, which examined food-duplicate samples from relatively urban areas in Fukushima (15,19). Local food supply in farming areas did not necessarily increase exposure to radiocesium because local municipalities routinely screen food products for personal consumption.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Nevertheless, these radiation levels were much lower than external radiation dose rates. Participants' residences neighbor the restricted and evacuation areas and participants consume homegrown vegetables; however, the doses were comparable to those in our previous research, which examined food-duplicate samples from relatively urban areas in Fukushima (15,19). Local food supply in farming areas did not necessarily increase exposure to radiocesium because local municipalities routinely screen food products for personal consumption.…”
Section: Discussionsupporting
confidence: 60%
“…The inhalation of airborne dust comprising resuspended radioactive deposits represents an additional route of internal exposure (17,18). For example, a survey in July 2011 showed that the radiocesium concentration in the air was on the order of 1 mBq/m 3 outside restricted areas (19).…”
Section: Significancementioning
confidence: 99%
“…Unfortunately, since additional or extended measurements except for Be-aerosols measured at various seasons during last six years with the same manner mentioned in the text radioactivity measurements could not been done on that occasion, all we can do in this stage is only a matter of speculation with scarce experimental evidence. There are several reports concerning size distributions of airborne radionuclides from the Fukushima accident [4][5][6][7][8][9]; in addition, for the Chernobyl accident there also exist comparable data [10][11][12][13][14][15]. For the measurements in Japan, the size distributions of radiocesium are partly different each other probably depending on the emission process from the reactors or transportation mechanism due to different sampling date and distance from the reactor site.…”
Section: Resultsmentioning
confidence: 99%
“…for the period from May to the end of 2011 Koizumi et al (2011) performed evaluations of doses by ingestion based on measurements made during a week in July 2011 in whole-day meal sets purchased in shops in four towns: Fukushima, Iwaki, Soma and Nihonmatsu. The doses evaluated were extrapolated by Koizumi et al over the course of a year; they range from "non-calculable" (activity below detection limits) to 80 µSv/an (in Soma).…”
Section: Ingestion Dose Estimatesmentioning
confidence: 99%